KNOWLEDGE, ATTITUDES AND PRACTICES RELATED TO PREVENT ORAL COMPLICATIONS DURING CHEMOTHERAPY AMONG PATIENTS ATTENDING AN ONCOLOGY CLINIC IN ROMANIA - Adriana Padure; Laura Cristina Rusu; Codruta Victoria Tigmeanu; Aureliana Caraiane; Marius Traian Leretter (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study Prevention and early management of oro-dental complications in cancer therapy will improve oral function and quality of life and reduce morbidity and cost of care. Oral hygiene was strongly recommended before cancer treatment, and preventive measures and oral care should be continued during and after cancer treatment. The aim of this study was to evaluate the level of patients' knowledge about the importance of oral hygiene and optimal dental status in order to minimize the occurrence of adverse effects during chemotherapy treatment in an oncology clinic in Romania. Material and methods A four-part questionnaire was used in the attempt to evaluate the prevalence of oral adverse effects during chemotherapy, knowledge, attitude and practices applied before and during treatment regarding the prevention and maintenance of oral and dental health. Results The results of this study show that 79.1% of patients presented at least one adverse effect in the oral cavity. Following the analyses, 8.3% of the patients declared that they had knowledge that the preventive oro-dental treatment was an integral part of the oncological pathway and only 2.7% of the patients followed preventive dental treatments before the cancer therapy. Conclusions The role of all medical specialties involved in cancer therapy is essential to educate patients to adhere to preventive treatments and strengthen their motivation in oral hygiene. The impact of complications in the oral cavity following cytostatic treatments is significant and interferes with the patient's quality of life.